If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -7 + 3x = 73 Reorder the terms: -7 + 7x + 3x = 73 Combine like terms: 7x + 3x = 10x -7 + 10x = 73 Solving -7 + 10x = 73 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 10x = 73 + 7 Combine like terms: -7 + 7 = 0 0 + 10x = 73 + 7 10x = 73 + 7 Combine like terms: 73 + 7 = 80 10x = 80 Divide each side by '10'. x = 8 Simplifying x = 8
| -5x+8+4x=6 | | x-2-2*ln(x)=0 | | s-10=20.81 | | 6k-10=14 | | 2y+15=23 | | 30m+350=25m+400 | | 6/34=t/108 | | X-4x=54 | | 18=10n | | 5y-3=47 | | 747+(-60x)=0 | | 6(x-8)+54=60 | | 42=49-v | | 2.02b+4.30=2.00b+6.30 | | 2(x)+4(y)=20 | | 5/9w=-1/4 | | 2(x)+4(y)=64 | | 6/24=t/108 | | 9(x+5)+8x=164 | | 747+(-60)=300 | | x(x+12)=(x-4)2 | | X+750=3200 | | x=26-57 | | 5(3x+2)=-3(2x-4)-4x | | 174=121-w | | 31=-4x-5x-5 | | 2e^4x+7=107 | | 182=42-y | | 9u+4u=30 | | 747+(-60)=0 | | 1/8x−49/8 | | 188=29-x |